Bioactive coating for tissue-engineered smalldiameter vascular grafts - V. A. Surguchenko; E. A. Nemets; V. Yu. Belov; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Objective: to develop a method for modifying composite small-diameter porous tubular biopolymer scaffolds based on bacterial copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and gelatin modified with a double-layered bioactive coating based on heparin (Hp) and platelet lysate (PL) that promote adhesion and proliferation of cell cultures.Materials and methods. Composite porous tubular biopolymer scaffolds with 4 mm internal diameter were made by electrospinning from a 1 : 2 (by volume) mixture of a 10% solution of poly(3-hydroxybutyrateco- 3-hydroxyvalerate) copolymer, commonly known as PHBV, and a 10% solution of gelatin, respectively, in hexafluoro-2-propanol. The structure of the scaffolds was stabilized with glutaraldehyde vapor. The scaffolds were modified with a bioactive Hp + PL-based coating. The surface morphology of the samples was analyzed using scanning electron microscopy. Biological safety of the modified scaffolds in vitro (hemolysis, cytotoxicity) was evaluated based on the GOST ISO 10993 standard. Interaction with cultures of human endothelial cell line (EA. hy926) and human adipose-derived mesenchymal stem cells (hADMSCs) was studied using vital dyes.Results. We developed a method for modifying small-diameter composite porous tubular biopolymer scaffolds obtained by electrospinning from a mixture of PHBV and gelatin modified with double-layered bioactive coating based on covalently immobilized Hp and human PL. The modified scaffold was shown to have no cytotoxicity and hemolytic activity in vitro. It was also demonstrated that the developed coating promotes hADMSC adhesion and proliferation on the external surface and EA.hy926 on the internal surface of the composite porous tubular biopolymer scaffolds in vitro.Conclusion. The developed coating can be used for the formation of in vivo tissueengineered small-diameter vascular grafts.